Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s13018-019-1203-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of platelet-rich plasma therapy in knee osteoarthritis does not depend on level of cartilage damage

Abstract: Objectives Osteoarthritis of the knee is common and often leads to significant physical disability. While classic conservative therapeutic approaches aim for symptoms like pain and inflammation, procedures like the intraarticular application of hyaluronic acids (HA) or platelet-rich plasma (PRP) are thought to stimulate the endogenous HA production, stop catabolism of cartilage tissue, and promote tissue regeneration. To analyse whether the positive effects of PRP injections are associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
(40 reference statements)
1
19
1
Order By: Relevance
“…Unfortunately, the included treated patients didn't show any signi cant improvements in the patellafemoral cartilage volume or meniscal disintegrity. In accordance, Burchard et al [32] suggested that intraarticular injection of PRP may improve symptoms of osteoarthritis and decrease pain in patients with knee joint osteoarthritis, independent of the level of cartilage damage quanti ed by the whole organ MRI scoring method. Furthermore, a study by Laudy et al [33] demonstrated that in patients with knee osteoarthritis, PRP injections resulted in decreased pain, improved function and global assessment, and changes in joint imaging.…”
Section: Discussionmentioning
confidence: 71%
“…Unfortunately, the included treated patients didn't show any signi cant improvements in the patellafemoral cartilage volume or meniscal disintegrity. In accordance, Burchard et al [32] suggested that intraarticular injection of PRP may improve symptoms of osteoarthritis and decrease pain in patients with knee joint osteoarthritis, independent of the level of cartilage damage quanti ed by the whole organ MRI scoring method. Furthermore, a study by Laudy et al [33] demonstrated that in patients with knee osteoarthritis, PRP injections resulted in decreased pain, improved function and global assessment, and changes in joint imaging.…”
Section: Discussionmentioning
confidence: 71%
“…This prospective case series aims to assess the effectiveness of ACP in clinical practice and to investigate the effect of sex, age, BMI, radiographic OA grade (Kellgren and Lawrence), history of knee trauma, and baseline Knee Injury and Osteoarthritis Outcome Score (KOOS) on clinical outcome. Since there is no consensus on whether PRP is more effective in mild or advanced OA (Lana et al 2016, Jubert et al 2017, Burchard et al 2019, we included patients with symptomatic OA of all grades. We hypothesize that treatment with ACP leads to clinically relevant improvement in KOOS 5 and that clinical outcome can be predicted with any of the investigated patient factors.…”
mentioning
confidence: 99%
“…We hypothesized that the improvement of both parameters (pain and function) were mainly due to control of the inflammation of the knee rather than the trophic effect of PRP on cartilage. This rationale is due to the fact that it has not yet been demonstrated that the improvement of knee function after PRP treatment correlates with a volume increase of the articular cartilage [ 38 40 ], even when has been demonstrated that in vitro, TGF-β1/3 can induce chondrogenesis of mesenchymal stem cells [ 41 ]. However, there is evidence that suggests that PRP has other effects on the joints other than the anti-inflammatory and this may probably explain why the group that received PRP had better results than the CS group.…”
Section: Discussionmentioning
confidence: 99%